THE USE OF POLYMERIC MATERIALS IN THE TREATMENT OF CORNEAL DISEASE - E.O. FILIPPOVA; A.S. CHERNYAKOV; N.M. IVANOVA (Avicenna Tajik State Medical University, 2019)
The article presents a critical assessment of the use of polymeric materials in keratoplasty, describing possible postoperative complications. The benefits and disadvantages of implanting various bio-compatible polymers: glyceryl-methacrylate, plastics ACR-7, plexiglass, polymethylmethacrylate, gelatin, hydrogel, and its modifications and others. The significant part of the article focuses on the use of biopolymers, many of which, according to studies, cause an inflammatory reaction, reorganization of collagen fibers and the change of the implant itself. A separate aspect of the article is the use of biodegradable polymers in keratoplasty. The great benefits of using these materials are the ability to control the rate of biodegradation by changing their structure by adding anions and cations superficially active substances. Of all the forms of polymers suitable for ophthalmology in keratoplasty, microspheres, films, and membranes have become very popular. Numerous studies using biodegradable materials have shown that despite the disadvantages (high cost, the complexity of manufacturing), of this type of polymers have great potential in the treatment of various corneal diseases.